Engineering functional skin constructs: A quantitative comparison of three‐dimensional bioprinting with traditional methods. Issue 4 (10th November 2021) - Li, Juyi; Fu, Shi; Lu, Kimberly W.; Christie, Olias; Gozelski, Michael T.; Cottone, Michael C.; Cottone, Philip; Kianian, Sara; Feng, Kuan‐Che; Simon, Marcia; Rafailovich, Miriam; Dagum, Alexander B.; et al.
Abstract: Tissue engineering has been successful in reproducing human skin equivalents while incorporating new approaches such as three‐dimensional (3D) bioprinting. The latter method offers a plethora of advantages including increased production scale, ability to incorporate multiple cell types and printing on demand. However, the quality of printed skin equivalents compared to those developed manually has never been assessed. To leverage the benefits of this method, it is imperative that 3D‐printed skin should be structurally and functionally similar to real human skin. Here, we developed four bilayered human skin epidermal‐dermal equivalents: non‐printed dermis and epidermis (NN), printed dermis and epidermis (PP), printed epidermis and non‐printed dermis (PN), and non‐printed epidermis and printed dermis (NP). The effects of printing induced shear stress [0.025 kPa (epidermis); 0.049 kPa (dermis)] were characterized both at the cellular and at the tissue level. At cellular level, no statistically significant differences in keratinocyte colony‐forming efficiency (CFE) ( p  = 0.1641) were observed. In the case of fibroblasts, no significant differences in the cell alignment index ( p  < 0.1717) and their ability to contract collagen gel ( p  = 0.851) were detected. At the tissue levels, all the four skin equivalents were characterized using histological and immunohistochemical analysis with no significant differences found in either epidermal basal cell count, thickness of viable epidermis, and relative intensity of filaggrin and claudin‐1. Our results demonstrated that 3D printing can achieve the same high‐quality skin constructs as have been developed traditionally, thus opening new avenues for numerous high‐throughput industrial and clinical applications. Abstract : Tissue‐engineered human skin constructs produced by traditional and 3D bioprinting methods showed similarity in epidermal differentiation, fibroblast orientation and tissue organization.